LITERASI KEUANGAN, TINGKAT PENDIDIKAN, MODAL USAHA, KEBERLANJUTAN USAHA DAN CATATAN KEUANGAN, PENGARUHNYA TERHADAP KINERJA UMKM: FINANCIAL LITERACY, EDUCATION LEVEL, BUSINESS CAPITAL, BUSINESS SUSTAINABILITY AND FINANCIAL RECORDS, ITS EFFECT ON MSME PERFORMANCE - Nurmawati, Nurmawati; Silfi, Alfiati; Mela, Nanda Fito; Abdurrahman, Rezi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
This study aims to determine and examine the effect of financial literacy, education level, business capital, business sustainability and financial records on the performance of MSMEs. This research was conducted in Aceh Singkil Regency. The sample used in this study was 100 MSME respondents registered at the Department of Industry, Trade, Cooperatives, and MSMEs in Aceh Singkil Regency with a random sampling technique. The results of this study indicate that Financial Literacy, Education Level, Business Capital, Business Sustainability, and Financial Records have a significant influence on the performance of MSMEs in Aceh Singkil Regency. The type of data used in this research is quantitative data. Then the source of data used in this study is primary data. Data collected by using a questionnaire. The data analysis technique used is SPSS, 26